Integrated modeling and analysis of an extendable double-link two wheeled mobile robot - Abdul Rahman, Muhammad Taqiuddin; Ahmad, Salmiah; Akmeliawati, Rini (2013)
This research is aimed to design and develop a two-wheeled mobile robot with an extendable link for applications in a confined area. The proposed system mimics a double inverted pendulum, where the first link (Link1) is made near to the upright position and the second link (Link2) can be at any interest angular position within [-90,90] range with the extendable effect. This type of configuration is very complex, highly nonlinear and less studied by the researchers in this field. Therefore this paper focuses on modeling of a multi degree of freedom of two-wheeled mobile robot. The mathematical model of the robot has been derived from its free body diagram involving the wheels, Link1 and Link2 with extendable effect. The equations have been linearised and represented in the form of state space model. The model was then tested using linear quadratic regulator (LQR), which was used to control the angular position of Link1. The results show that the model derived works very well with its linear operating region. The modeling stage was extended using virtual prototyping that represent its actual system. Simulation results also shown that with suitable controllers, the 4D model developed was able to perform at any interest angular position.